2002
DOI: 10.1002/1521-396x(200211)194:1<338::aid-pssa338>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Study of ZnSe Single Crystals Obtained by Solid Phase Recrystallization under Different Pressure Conditions. Effects of Thermal Treatment

Abstract: ZnSe single crystals, obtained by the Solid Phase Recrystallization (SPR) method under three different pressure conditions, 10 and 5 atm of Se, and 2 atm of argon, have been investigated by means of photoluminescence (PL) and optical microscopy. Special attention has been paid to the surface state of the samples. Samples recrystallized under 10 atm of Se present the best rate between the PL response for the excitonic zone and the deep level one that shows a “clean” PL emission without significant peaks and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In fact, the PL of ZnSe crystals or thin films is usually reported to occur at 442 nm for band gap emission or 500−560 nm for doped ion emission . On the other hand, the lower energy emission of about 2.08 eV from ZnSe microcrystals was assigned to self-activated luminescence, probably as a result of some donor−acceptor pairs related to Zn-vacancy and interstitial states . Similarly, the strong emission from the present ZnSe nanostructures indicates the influence of Zn-vacancy and interstitial states, the nature of which is not clear or worthy of further study.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…In fact, the PL of ZnSe crystals or thin films is usually reported to occur at 442 nm for band gap emission or 500−560 nm for doped ion emission . On the other hand, the lower energy emission of about 2.08 eV from ZnSe microcrystals was assigned to self-activated luminescence, probably as a result of some donor−acceptor pairs related to Zn-vacancy and interstitial states . Similarly, the strong emission from the present ZnSe nanostructures indicates the influence of Zn-vacancy and interstitial states, the nature of which is not clear or worthy of further study.…”
Section: Resultsmentioning
confidence: 73%
“…Wide-gap II−VI semiconductors are efficient emitters in the blue to ultraviolet spectral region, and excitons in these compounds are much more stable than those in the conventional III−V semiconductors that are widely used for optoelectronic applications. , Recent studies showed that the low-dimensional nanostructures of Zn-based II−VI wide-gap semiconductors exhibit exciton binding energies exceeding their optical phonon energies. As a consequence, the quantum yield of the II−VI-based devices is expected to be comparable to or greater than that of the common III−V devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PL spectra of untreated and lasertreated areas of the ZnSe sample under an excitation of 337 nm (3.68 eV) are presented in Figure 3. The PL band at 445.2 nm (2.78 eV) attributed to the excitonic recombination at Zn vacancy-related acceptors [39] and wide PL band at about 461.3 nm (2.687 eV) reveal noticeably higher intensity for the untreated area of the ZnSe sample in comparison to the fs-laser-treated area whereas the bands in the region from 500 to 700 nm are of the same order of magnitude (see Figure 3). For one of the fs-laser-treated areas of the ZnSe sample, the PL band at about 462.3 nm (2.68 eV) demonstrates the nonelementary character under the laser excitation at 337 nm.…”
Section: Peculiarities Of Lipss Formation On the Znse Surfacementioning
confidence: 96%
“…We can only notice hardly observable shoulder of 463.7 nm at the slope of the band. It may indicate that the high structural perfection of ZnSe single crystal is not affected significantly during fs-laser processing, while some structural defects could be produced and/or not removed by the mechanical polishing [39].…”
Section: Peculiarities Of Lipss Formation On the Znse Surfacementioning
confidence: 99%